Journey to Lupan-On a graphic novel - Arre, Arnold (Tuttle Publishing [2022], 2022)
The Mythology class friends thought they were safe from the Dark Anitos, but now the evil Budniaan has arrived in their world with his army of zombie warriors and demented engkantos demons, and their lives are once again at stake. With Rey and Misha on the other side of the globe and the group at odds over what to do, the one course they can all agree on is the inevitable one--reunite and combine their strengths to thwart Budiaan's threat. Revisiting a scene of their past triumphs, the group uncovers an ancient artifact. Will it lead them to the safety of the Skyworld, the spirit realm? Will this group of intrepid adventurers be able to summon the spirit of resistance that once defined them? As the most powerfully evil force they've ever faced reaches their borders, they're not really given a choice!